2020
DOI: 10.1186/s13020-020-00405-y
|View full text |Cite
|
Sign up to set email alerts
|

Catechins from oolong tea improve uterine defects by inhibiting STAT3 signaling in polycystic ovary syndrome mice

Abstract: Background It is showed that inflammation is causative factor for PCOS, leading to a decline in ovarian fertility. Previous studies have reported that tea consumption can reduce the incidence of ovarian cancer. We speculate that catechins from oolong tea (Camellia sinensis (L.) O. Kuntze) may have a potential therapeutic effect on PCOS. This study aims to investigate the effects of oolong tea catechins on the uterus of polycystic ovary syndrome (PCOS) mice induced by insulin combined with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“… Other health functions include antioxidant, anti-inflammatory, immuno-regulatory, anti-cancer, anti-obesity, anxiety reduction, cognitive enhancement, anti-bacterial, anti-viral, and anti-COVID-19 activities, etc. It has been found that catechins from oolong tea can improve the ovarian functions in polycystic ovary syndrome mice [ 182 ] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Other health functions include antioxidant, anti-inflammatory, immuno-regulatory, anti-cancer, anti-obesity, anxiety reduction, cognitive enhancement, anti-bacterial, anti-viral, and anti-COVID-19 activities, etc. It has been found that catechins from oolong tea can improve the ovarian functions in polycystic ovary syndrome mice [ 182 ] …”
Section: Discussionmentioning
confidence: 99%
“…It has been found that catechins from oolong tea can improve the ovarian functions in polycystic ovary syndrome mice [ 182 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechins of oolong tea alleviate polycystic ovary syndrome (PCOS) in mice induced by insulin combined with human chorionic gonadotropin. The catechins reduced E2, FSH, and LH levels in the blood and the ratio of LH/FSH, downregulated MMP-2, MMP-9, and p-NF-κB p65 in the blood the uterus and improve glucose metabolism and insulin resistance [ 157 ]. Signal networking analysis has shown the potential links of several genes, including NF-κB activation and autophagy-related genes during PCOS.…”
Section: Herbal Teas and Autophagymentioning
confidence: 99%
“…Individualized treatment remains the main approach, but grouping the phenotypes and following therapeutic recommendations may also prove to be clinically suitable. Precise recommendations should be implemented long before metabolic complications occur, which is particularly important for women with PCOS as they are predisposed to developing endometrial and ovarian cancer [ 5 , 6 ]. Therefore, the therapeutic approaches aimed at using anti-inflammatory remedies in supplementing and supporting anticancer therapy are crucial.…”
Section: Introductionmentioning
confidence: 99%